Activated hydrogen influence on characteristics of penning discharge with hollow cathode - Borisko, V.N.; Klochko, Ye.V.; Sereda, I.N.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2006)
The results of experimental investigations of reflective discharge using sectioned hollow cathode are presented. As constructive elements of the hollow cathode an alloy Zr₅₀V₅₀Hx able to absorb hydrogen reversibly under low pressure was used. It has been shown that in case of applying of metal-hydride hollow cathode the penetration of plasma in the hollow occurs sufficiently deeper. The possibility to operate the plasma penetration into the hollow cathode by means of potential variation on its sections was investigated. The peculiarities of energy distribution function of extracted ions were carried out. Представлены результаты экспериментальных исследований отражательного разряда с секционированным полым катодом. В качестве конструкционных элементов полого катода использовался геттерный сплав Zr₅₀V₅₀Hx, способный к обратимому поглощению водорода при низком давлении. Показано, что применение такого материала приводит к значительно большему проникновению плазмы в катодную полость. Исследована возможность управления проникновением плазмы в металлогидридный полый катод путем варьирования потенциалами на его секциях. Исследованы особенности функции распределения извлекаемых ионов из такого разряда. Представлено результати експериментальних досліджень відбивного розряду з секціойованим порожнистим катодом. В якості конструкційних елементів порожнистого катоду використовувався гетерний сплав Zr₅₀V₅₀Hx, що здатен оборотно поглинати водень при низькому тиску. Показано, що застосування такого матеріалу приводить до значно більшого проникнення плазми в катодну порожнину. Досліджено можливість керування проникненням плазми в металогідридний порожнистий катод шляхом варіювання потенціалами на його секціях. Досліджено особливості функції розподілу іонів, що витягаються з такого розряду.